Types of city dwellersвЂ™attitudes towards service robots in the city of Perm - Gyuzel I. Seletkova; Olga A. Burova; Olga A. Ganina; Elena V. Seredkina (Социологическая наука и социальная практика, 2023)
The effectiveness of robot implementation in various societal sectors depends not only on the robot’s technical characteristics but also on how different social groups perceive and interact with them. Social attitudes towards robots, in turn, are influenced by sociocultural and sociodemographic factors. In the context of the sociology of technology and actor-network theory, this research explores the social significance of technical devices, the processes of social adaptation, and communication with robots. However, empirical research on human-robot interaction (HRI), especially in the Russian context, remains limited. This article presents the results of a study that examines the perceptions of robots by actual and potential users in two aspects: the level of basic social attitudes towards new technologies and robots (social acceptability) and the evaluation of interactions with robots in specific situations (practical acceptability). The empirical basis of the study consists of survey data from customers at a multifunctional center providing state and municipal services in Perm. They received services from either a service anthropomorphic robot, Promobot V.4, or a human employee at the center. Using cluster analysis, three types (clusters) of attitudes towards innovations and robots were identified at the level of basic social attitudes: robo-skeptics, robo-phobes, and robo-philes. The social characteristics of these identified types were examined. The study introduces an original method for measuring satisfaction with actual interactions with service robots based on various parameters (evaluation of service convenience, communication quality, personal activity, willingness to recommend robot services, etc.). The study confirms the hypothesis of the connection between the type of attitude towards innovations and robots and the satisfaction with actual interactions with robots in specific situations. The lowest levels of satisfaction with robot interactions and the desire to avoid such interactions were observed among robo-phobes, who are more frequently represented by individuals of senior age group (age 55 and above). The research results allow determining the prospects for implementing service robots in the public space of a major Russian city based on understanding the social attitudes of users.